Realisasi Pendidikan Karakter Melalui Kepanduan Hizbul Wathan - Saputro, Fathan Faris (STAI Muhammadiyah Paciran Lamongan, 2024)
The nature of a country is reflected in the people who live there. Considering that children are skilled imitators, it is important to instill character education in them from an early age. A child's progress will contribute to the nation's positive outlook on life in the future. On the other hand, the personality of a nation will also be bad if the younger generation has bad character. The Hizbul Wathan (HW) scouting movement provides a platform for developing student character in schools affiliated with Muhammadiyah. This research aims to explain the implementation of character education through HW scouting activities. The approach used in this research is a qualitative approach with case study. The research site is MI Muhammadiyah 2 Solokuro students from grades 3 to 6 who are active in taking part in HW scouting activities. The research findings show how character education initiatives through HW scouting activities are carried out regularly, through lectures and punishments. With this research, it is believed that character education in Indonesia will become more advanced in the future, one way is through HW scouting which is one way to make the country smarter.